Math Clock: Perangkat Penunjuk Waktu Kreatif untuk Olahraga Otak - Galuh Boy Hertantyo; Oky Dwi Nurhayati; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
Brain is one of the most vital parts for humans, with the number of brain function that is needed for the body, the brain becomes a very important part of the human body. If there is damage to the brain will certainly cause the performance of the human body will not run properly. Because of that, it’s very important to maintain brain health. There is a way to maintain brain health, for example is by doing brain exercise. Examples of brain exercise is to do simple math calculations or doing brain games like sudoku. Because of that, created a tool that can help the brain to maintain brain exercise. The tool is called math clock. Making math clock tool consists of hardware and software. The hardware consists of RTC as real time data input, ATmega328 as microcontroller and dot matrix 32x16 as a tool to display the output that has been processed by the microcontroller. The software is built using C with Arduino IDE. Math clock will process the data from RTC then processed it, in microcontroller so when output displayed on dot matrix, output will be simple mathematical operation with real time clock data on it. Test results show that, math clock is capable of displaying a simple mathematical calculation operations such as addition, subtraction, multiplication and division. The mathematical operation that display on math clock, appears to be random, so it’s not triggered by same mathematical operation. In math clock the display will change every 20 second, so in 1 minute there are 3 different kinds of mathematical operations. The results of questionnaires of 10 different students, showed 9 out of 10 students said math clock is a tool that easy to use as a clock. Math clock will be alternative for doing brain exercise every day.